OPERATIONAL EFFICIENCY AS A MODERATOR OF THE IMPACT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) ON FINANCIAL PERFORMANCE: AN EMPIRICAL STUDY OF NON-FINANCIAL COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2014 TO 2023 - Khanif Nur Fathurohman; Gatot Nizar Ahmad; ⁠Agung Dharmawan Buchdadi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the influence of Environmental, Social, and Governance (ESG) on the company's financial performance, as well as test the role of operational efficiency as a moderation variable in this relationship. The research object includes non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2014–2023. ESG variables are measured using Bloomberg's ESG score which includes environmental, social, and governance dimensions, while operational efficiency is proxied by the Total Asset Turnover ratio. Financial performance is proxied by Return on Assets. The research method uses a quantitative approach with panel data regression analysis. The research sample consisted of 80 companies with a total of 711 observations. The results of the study show that ESG has a significant negative effect on financial performance. However, operational efficiency has been shown to play a role as a moderation variable that strengthens the relationship between ESG and financial performance. This research makes a theoretical contribution by enriching the literature on the relationship between ESG and financial performance, especially in the context of emerging markets. From a practical perspective, the results indicate that the implementation of ESG will only create financial value if integrated with internal efficiency strategies. Thus, companies are advised to not only focus on compliance with ESG aspects, but also ensure efficient management of resources to increase long-term profitability.